2012
DOI: 10.1007/978-3-642-28537-0_19
|View full text |Cite
|
Sign up to set email alerts
|

A Hands-on Look at Active Probing Using the IP Prespecified Timestamp Option

Abstract: In the last years, network measurements have shown a growing interest in active probing techniques. Recent works propose approaches based on the IP prespecified timestamp option and consider its support to be enough for their purposes. On the other hand, other works found that IP options are usually filtered, poorly implemented, or not widely supported. In this paper, to shed light on this controversial topic, we investigate the responsiveness obtained targeting more than 1.7M IPs using several probes (ICMP, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The large-scale applicability of the IP timestamp option has been evaluated and it has been shown that using this option is only effective for 12.9% of the destinations [111]. Note that it seems that using the IP timestamp option is a little bit more effective in the context of reverse traceroute (see Sec.…”
Section: Active Methodsmentioning
confidence: 99%
“…The large-scale applicability of the IP timestamp option has been evaluated and it has been shown that using this option is only effective for 12.9% of the destinations [111]. Note that it seems that using the IP timestamp option is a little bit more effective in the context of reverse traceroute (see Sec.…”
Section: Active Methodsmentioning
confidence: 99%
“…In a previous work [11], thanks to a large-scale measurement campaign targeting more than 1.7M IP addresses, we observed that the routers managing the TS option in the Internet can be classified in the two main categories reported below (interested readers may also refer to a CAIDA online report [26] for more details).…”
Section: Ts Option and Router Behaviorsmentioning
confidence: 99%
“…In this work, inspired by a previous technique [9] and the experience gathered by experimenting with IP options [10][11][12], we present, evaluate and release Pythia, a novel alias resolution technique based on active probing. Pythia exploits a combination of (i) IP Prespecified Timestamp option [13] and (ii) UDP packet probes to reconstruct a specific category of routers, we named any-interface stamping routers, representing about one tenth of the devices in the Internet according to previous works [10,11] (Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This option has 2 been used to identify the addresses owned by the same network device [31], to develop a reverse Traceroute [32], to estimate the network delay [33] and to detect third-party addresses in Traceroute IP paths [26]. A deep study on the level of support for this option is reported in [34]. While we foresee more and more applications, in this work we use the TS option to count the IP modules managing the IP option on the path: DRAGO exploits the TS option to identify incongruities between the number of IP modules decrementing the TTL and those managing the option.…”
Section: Introductionmentioning
confidence: 99%